Capitalist Reality and the (need for a) Utopian Realism - Mais, Christos (Design/Arts/Culture, 2023)
Capitalist realism is globally dominant. This article argues that this teleology is closely related with Francis Fukuyama’s “end of history” and that this combination prescribes a dystopian present and future. By revisiting “utopian” visions in history, such as in the struggles of Ernesto “Che” Guevara or Mao Zedong, or in literature, as in the works of Jules Verne or Alexander Bogdanov, I propose that we need to revisit utopia in terms of politics as well as in terms of fiction.